Inclusion body hepatitis in Greece - Bεϊμος, Γ.; Παπανικολάου, Ι.; Παπαδόπουλος, Χ. (Journal of the Hellenic Veterinary Medical Society, 2019)
Two cases of Inclusion Body Hepatitis in chickens diagnosed for the first time in Greece, are described. The disease was observed on December 1973 and the Spring of 1973 on 5 - 6 weeks old broilers. The duration was 12 - 20 days and 10 and 20% mortality respectively. Attempts for virus isolation were negative as well as serum tests for other diseases, while from birds of the second case Coli were isolated. Histological examination revealed the presence of nuclear inclusion bodies of Cowdry- A type in the liver cells bone marrow degeneration, nephrosis and hypoplasia of the bursa of Fabricius. Diagnosis was based on the presence of inclusion bodies in relation with the clinical and necroscopic data.